A bi-objective optimization for integrated truck operation and storage allocation considering traffic congestion in container terminals. (1st February 2023) - Tao, Yi; Zhang, Shiling; Lin, Changhui; Lai, Xiaofan
Abstract: In this work, we are concerned with the traffic congestion issue of internal trucks in busy transshipment container terminals. It is well known that traffic congestion contributes a major part of pollutant emissions in terminals and thus needs to be effectively mitigated. To deal with it, the workload balancing protocol is incorporated and the concept of neighboring subblocks is introduced. Based on this, we study the integrated planning problem of truck operation and storage allocation and a bi-objective optimization model is proposed to minimize the travel distances of trucks and the degree of workload imbalance in the course of moving transshipment containers. A NSGA II based method is designed and extensive experiments are conducted on real-life test instance to show the performance of the solution approach. Trade-off between two objectives is identified and analyzed. Moreover, pollutant emissions caused by trucks' transportation and traffic congestion are evaluated and discussions are also provided.